Performance and proposal of reproductive management in European quails - Nayra de Paula Montijo de Oliveira Barbosa; Daniel Dantas Pereira; João Vitor Santana Prates; Fabiana Ferreira; Felipe Gomes Silva; André Luiz Mendes Athayde; Letícia Ferrari Crocomo (Ciência Animal Brasileira)
The objective of this study was to verify posture, fertility, and embryonic viability depending on the time and frequency use of the male for reproduction, as well as evaluate sperm storage time in the female after copulation in European quails. For this, 180 males were used (18 males mated with 10 females each). The experimental design was completely randomized in a 2x10 factorial scheme, with two genetic lineages and ten days of use for couples, with 14 replications. Males remained in copulation for ten consecutive days, mating each day with a different female. Information on egg laying, embryonic viability, and egg fertility was collected daily for fourteen days after copulation. The time males remained in copulation did not alter the egg fertility. In females, the presence and possible stress caused by males did not change the laying rates and eggs’ embryonic viability. The fertility rate was higher than 70% only three to five days after copulation, not achieving the same performance on other days. Based on these observations, a more efficient reproductive management proposal for large populations may be implemented using three females for each male on alternate days, with egg collection starting on the third day after the first copulation, with the necessity of another copulation every three days per female, considering the mating period of 10 consecutive days. For smaller breeding stocks, the ratio of two females for one male may be used as an alternative, considering a rest day for the male.